1990
DOI: 10.2307/3586851
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Complexity of Revising across Languages

Abstract: Although previous research in ESL composition suggests a link between writing in a first and second language, few studies have investigated this relationship in the context of the revising process. This article examines revision in controlled L1 and L2 writing tasks. Four advanced ESL writers with differing first language backgrounds wrote two argumentative essays in their native languages and two in English. Revisions were then analyzed for specific discourse and linguistic features. The results, for the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
1
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 11 publications
11
76
1
4
Order By: Relevance
“…Unlike the less skilled writers, whose attentional resources are consumed by surface-level issues, skilled writers do global changes to their first draft (Schriver, 1990;Sommers, 1996; van Gelderen, 1997; Wallace & Hayes, 1991;Witte, 1985). The findings also agree with the results of studies carried out on second language writers revising strategies (e.g., Hall, 1990;Krashen, 1984;Roca De Larios et al, 2002;Porte, 1997;Victori, 1999). Bridwell (1980) also noted significant differences in the revising practices of skilled and unskilled writers; she reported that good writers revised more while writing their initial drafts and mainly revised at the deep level.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Unlike the less skilled writers, whose attentional resources are consumed by surface-level issues, skilled writers do global changes to their first draft (Schriver, 1990;Sommers, 1996; van Gelderen, 1997; Wallace & Hayes, 1991;Witte, 1985). The findings also agree with the results of studies carried out on second language writers revising strategies (e.g., Hall, 1990;Krashen, 1984;Roca De Larios et al, 2002;Porte, 1997;Victori, 1999). Bridwell (1980) also noted significant differences in the revising practices of skilled and unskilled writers; she reported that good writers revised more while writing their initial drafts and mainly revised at the deep level.…”
Section: Resultssupporting
confidence: 86%
“…Phooi (1986), too, noted that the Chinese university students in his study frequently focused on cognitively easier word level changes like deletions, additions, and substitutions. Also, Hall (1990) reported that advanced EFL writers either made revisions that did not change the meaning of sentences or local changes that were restricted to word and phrase level. And finally, Moon (2000) conducted a research with EFL learners aged between ten and twelve and reported that addition at word and sentence level was the most common revising practice, though adding new sentences did not lead to inclusion of new ideas to the previous meaning.…”
Section: Theory and Practice In Language Studies 787mentioning
confidence: 99%
“…Most of what we know about L2 learners' revision practices has come from three types of studies: those that examine students' L2 composing processes (Raimes, 1987;Zamel, 1982); those that compare L2 learners' revision processes and outcomes in the L1 and the L2 (Hall, 1990); and those that compare the revision practices of skilled and unskilled L2 writers (Porte, 1996(Porte, , 1997. These studies use think-aloud protocols to examine writers' revision processes and holistic scores to assess the quality of their revised texts.…”
Section: Revision In L1 and L2mentioning
confidence: 99%
“…Where differences between L1 and ESL writing are concerned, studies were conducted to investigate the composing process (Hall, 1990), written texts (Cook, 1988), correlations between Ll and ESL writing ability (Cook, 1988), organizational pattern (Hirose, 2003), word identifications (Wang & Coda, 2007), and written text features including fluency, accuracy, and quality. As for fluency, many studies (e.g., Silva, 1990) reported that texts written in English were shorter.…”
Section: Review Of Related Studiesmentioning
confidence: 99%